2018
DOI: 10.1002/ijc.31344
|View full text |Cite
|
Sign up to set email alerts
|

Associations of metabolic syndrome and C‐reactive protein with mortality from total cancer, obesity‐linked cancers and breast cancer among women in NHANES III

Abstract: Although metabolic syndrome (MetS) is a prognostic factor for cancer occurrence, the association of MetS and cancer mortality remains unclear. The purpose of this study was to evaluate whether MetS, components of MetS and C-reactive protein (CRP) are associated with cancer mortality in women. A total of 400 cancer deaths, with 140 deaths from obesity-linked-cancers (OLCas), [breast (BCa), colorectal, pancreatic and endometrial], linked through the National Death Index, were identified from 10,104 eligible subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 48 publications
(77 reference statements)
6
25
1
Order By: Relevance
“…Our findings are consistent with those from previous studies [24,25,29,30]. In a cohort of 4,216 eBC patients, the presence of MetS at diagnosis was associated with a 1.5-fold increased risk of recurrence or second primary BC and 1.65-fold increased risk of BC-specific mortality compared with patients with no MetS [24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with those from previous studies [24,25,29,30]. In a cohort of 4,216 eBC patients, the presence of MetS at diagnosis was associated with a 1.5-fold increased risk of recurrence or second primary BC and 1.65-fold increased risk of BC-specific mortality compared with patients with no MetS [24].…”
Section: Discussionsupporting
confidence: 92%
“…In a cohort of 4,216 eBC patients, the presence of MetS at diagnosis was associated with a 1.5-fold increased risk of recurrence or second primary BC and 1.65-fold increased risk of BC-specific mortality compared with patients with no MetS [24]. Similarly, a study in 10,014 patients reported twofold increase in BC mortality with MetS [30], while another study (N = 288,834) reported a 23% higher risk of BC mortality in only older (> 60 years) women with MetS without any impact in younger patients [25]. Interestingly, MetS also correlated with an enhanced risk of new BC events (defined as loco-regional recurrences, distant metastasis or new primary BC) in a prospective study using 2,092 eBC patients; however, an impact on survival was not evaluated [29].…”
Section: Discussionmentioning
confidence: 92%
“…; Gathirua‐Mwangi et al. ). On the other hand, exercise inhibits inflammation in adipose tissue and creates unfavorable conditions for cancer, (Dieli‐Conwright et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Gathirua‐Mwangi et al. ; Guo et al. ) and it has been hypothesized that this may be due to a mild proinflammatory state and attenuated immune response (Khan et al.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that higher baseline fasting serum concentrations of glucose, insulin, and insulin resistance were all independently associated with pancreatic cancer after adjusting for age, smoking and body mass index 42. These reports were in line with the independent effects of WC and fasting level of glucose for pancreatic cancer development found in our study.A disturbed inflammatory status might play an important role in mediating the putative tumorigenesis of MetS 43. In the present study,the HRs increased when MetS and CRP were jointly (MetS / CRP ≥1.00 mg/dL, HR = 1.55) assessed for risk of pancreatic cancer compared to when MetS was assessed alone (MetS / CRP < 1.00 mg/dL, HR = 1.44) or CRP was assessed alone (No MetS / CRP ≥1.00 mg/dL, HR = 1.19).…”
mentioning
confidence: 99%